Model Pengembangan Sistem Informasi Akuntansi Taman Pendidikan Alquran - Nurbatin, Defia (Jurnal Ekonomi Modernisasi, 2017)
The purpose of this research to generate models of Accounting System in the form of Standard Operating Procedures (SOP) for guidance on the accuracy of management information for the management TPQ Al-Hidayah Dau Malang. The research phase starting from problem identification, data collection, preparation of the product, product testing (validation expert) and penyepurnaan final product. Data collection techniques that focus group discussions, observation, interview and questionnaire (questionnaire). Questionnaire as an expert validation instrument consists of four aspects, namely ratings aspects of usability, simplicity, completeness and legibility. The technique used to analyze data on the validation of scoring is to use the average value of the test. The study produced a quality system in the form of 10 SOP Flow Information Financial Recording and 8 SOP Flow of Information Management and Financial Control that shows the application of SOP has to be implemented and the feasibility of value according to user needs.